Internal metal(loid)s are potentially involved in the association between ambient fine particulate matter and blood pressure: A repeated-measurement study in north China. (March 2021) - Lan, Changxin; Liu, Yingying; Li, Qi; Wang, Bin; Xue, Tao; Chen, Junxi; Jiangtulu, Bahabaike; Ge, Shufang; Wang, Xuepeng; Gao, Miaomiao; Yu, Yanxin; Xu, Ying; et al.
Abstract: The effects of ambient fine particulate matter (PM2.5 ) exposure on blood pressure have been widely reported. However, there remains uncertainty regarding the underlying roles of particulate matter components. We aimed to investigate the association between ambient PM2.5 exposure and blood pressure, as well as the potential effects of trace metal(loid)s, in a repeated-measurement study that enrolled women of childbearing age. Our study included 35 participants from Hebei Province, China, each of whom was visited for five times. During each visit, we conducted questionnaire surveys, measured blood pressure, and collected blood. The daily PM2.5 exposure of participants was estimated according to their residential addresses using a spatiotemporal model that combined monitoring data with satellite measurements and chemical-transport model simulations. This model was used to calculate average PM2.5 concentrations in 1, 3, 7, 15, 30, and 60 days prior to each visit. Serum concentrations of various trace metal(loid)s were measured. A linear mixed-effects model was used to investigate associations among study variables. Overall, the mean (standard deviation) 60 days PM2.5 concentration over all five visits was 108.1(43.3) μg/m 3 . PM2.5 concentration was positively associated with both systolic and diastolic blood pressures. Likewise, ambient PM2.5 concentration was positively associated with serum concentrations of manganese and arsenic, and negatively associated with serum concentrations of nickel, tin, and chromium. Only the serum concentration of molybdenum was negatively associated with systolic blood pressure. We concluded that ambient PM2.5 exposure may contribute to elevated blood pressure, potentially by interfering with internal intake of various metal(loid)s in the human body. Graphical abstract: Image 1 Highlights: We investigated the association between PM2.5 exposure and blood pressure (BP). A repeated measurement design was adopted for the 35 childbearing-age woman. Their serum concentrations of various metal(loid)s were analyzed using ICP-MS. Systolic and diastolic BPs were positively associated with PM2.5 exposure. PM2.5 exposure may affect the serum metal(loid) levels of Mn, Ni, Sb, Cr and As.